Analisis Kualitas Perairan Dan Hubungannya Dengan Struktur Ekosistem Danau Jakabaring Sport City Palembang - Handaiyani, Sapta; Hidayat, Saleh; Mukharomah, Ervina (Indobiosains, 2025)
Jakabaring Sport City Lake plays an important role in maintaining the balance of the habitat ecosystem by improving environmental quality and ecological, recreational and sports functions. Based on Google Map, JSC Lake is 2.1 km long and the width of the lake is 185 m at the base, 714 m at the middle and 178 m at the end. Studies regarding the analysis of water quality and ecosystems with the structure of the JSC lake ecosystem itself are still very minimal. This research uses quantitative descriptive methods. Selection of station locations using purposive sampling. The research results show that the water quality of Lake JSC Palembang is in the good category. This is supported by research data which shows that there are still quite a variety of plants, namely 12 identified species including Lagerstroemia indica, Eichhornia crassipes, Hydrilla verticillata, Cocos nucifera, Mimosa pudica, Pinus merkusii, Cerbera odollam, Alstonia Scholaris, Passiflora foetida, Asystasia gangetica, Cyperus rotundus, Nymphaea rubra and also microorganisms such as Seven species of phytoplankton were still found, namely Eudorina sp, Gonium, Oscillaroria limosa, Pandorina sp, Pediastrum duplex, Scenedesmus acutus, and Tetradesmus wisconsinnensis from 3 observation stations.